Exploring Multidimensional Engagement And Its Influence On Visitor Satisfaction In Single Artist Concert Settings - Adnan Zaidan Eka Saputra (Journal of Business on Hospitality and Tourism, 2025)
This study examines how different dimensions of engagement shape visitor satisfaction in the context of single artist concerts a form of live music event that has received limited scholarly attention despite its growing cultural relevance. The purpose of the research is to understand the roles of emotional cognitive physical and novelty related aspects of experience in forming audience evaluations. A quantitative approach was applied using an online survey completed by individuals who had attended at least one single artist concert with data analyzed through a variance based structural modeling technique. The findings reveal that emotional and cognitive engagement are the primary contributors to satisfaction while physical engagement and perceived novelty show minimal influence. These results provide new insight into how visitors interpret focused live music experiences and highlight the need to consider event specific experiential structures in concert research.